Efecto de la densidad de plantación sobre la resistencia al corte y compresión paralela a las fibras en madera de Eucalyptus grandis Hill (ex Maiden) de 11 años de edad = Effect of planting density on shear strength and compression parallel to the fibers in wood of Eucalyptus grandis Hill (ex Maiden) 11 years old - Bragañolo, Adelaida (2023)
Certain uses of wood make the mechanical properties of wood relevant. Therefore, it is important for the forester to know the characteristics of the wood to be obtained according to the adopted silvicultural management. The influence of initial planting density on shear strength and compression axial or parallel to the fibers was studied in 11-years-old Eucalyptus grandis wood. The evaluated treatments did not significantly influence the studied mechanical properties, presenting differences between the